Effect of analysts' earnings pressure on environmental information disclosure of firms: Can corporate governance alleviate the earnings obsession? - Ming Zhang; Aiqun Wang; Shuya Zhou (Borsa İstanbul Review, 2023)
Analysts' earnings pressure not only drives corporate managers to improve short-term financial performance but also encourages them to engage in myopic decisions detrimental to environmental performance. However, evidence on whether analysts' earnings pressure affects environmental information disclosure of firms is limited. Hence, we explore the effect of analysts' earnings pressure on corporate environmental information disclosure using panel data on environmental information disclosure of Chinese listed firms covering from 2013 to 2019. The results suggest that firms with higher analysts' earnings pressure have lower levels of environmental information disclosure. The abatement of environmental expenditure is the main mechanism of the negative effect of analysts' earnings pressure on environmental information disclosure. Furthermore, firms with lower pressure-sensitive institutional ownership and ownership concentration and higher proportions of independent directors and securities background directors are less likely to reduce the levels of environmental information disclosure in response to analysts' earnings pressure. Our results not only facilitate recognizing the hindering factors of corporate environmental information disclosure but also provide insights for urging firms under earnings pressure to disclose high-level environmental information and realize sustainable green development.
Keywords: G10; G32; G34; Q56; 330; Analysts' earnings pressure; Environmental information disclosure; Environmental expenditure; Corporate governance; Ownership structure; Board characteristics